Relationships between the wellness of older adults, health status, participation, and social determinants of health: a cross-sectional analysis using the National Health and Aging Trends Study - Parenti, Victoria, author; Graham, James, advisor; Schoessow, Kim, committee member; Miller, Ray, committee member (Colorado State University. Libraries, 2022)
Objectives: The primary objective of the current study is to explore the independent effects of different types of health and participation variables on subjective well-being among community-dwelling older adults. A secondary objective is to examine the roles that social determinants of health, including environmental, economic, and social factors, may play in mediating those relationships. Data Source: The National Health and Aging Trends Study (NHATS) includes survey data from a large, nationally representative sample of Medicare beneficiaries ages 65 and older. The data capture a snapshot of later-life functioning, including information on health conditions, self-care, well-being, participation, living arrangements, and many more. NHATS data were developed for public use and have been used in more than 400 scientific publications. Participants aged 65 and older were drawn from Round 9 of NHATS conducted in 2019. Methods: Participants were included in the final sample if they resided in the community and completed a sample person interview (no proxy person interviews were included). Main variables being assessed include the 11 items of Well-Being, hospitalizations, general self-rated health, depressive symptoms, and participation in social activities. Proxy variables from the NHATS were selected to represent the individual domains of the social determinants of health, including economic stability, education, healthcare access, social and community context, and neighborhood and built environment. Bivariate and regression analyses were conducted to explore independent relationships and mediation effects. Results: The data indicate that hospitalizations, self-rated health, depressive symptoms, and participation in social activities are independently associated with subjective well-being. Additionally, indicators for economic stability, education, health literacy, and community context were independently associated with well-being among the sample of Medicare beneficiaries. There was one mediating effect of an individual SDOH domain on the relationship between hospitalizations and subjective well-being after conducting the regression analysis. Conclusion: The results from the current study contribute to a growing body of literature examining relationships between several factors and well-being outcomes for community-dwelling older adults. Data from the current study provide substantial insight on how health status, participation, and SDOH indicators can be used in future research to explore these relationships, and identify populations at risk for occupational justice or health inequities. Future research is warranted to validate measures and indicators of SDOH to further explore their relationships with health and well-being outcomes using national data sets.
Keywords: health; participation; well-being; older adults; community; social determinants of health